Increasing students’ engagement: The use of new instructional designs in English literature online courses during COVID-19 - Awajan, Nasaybah (Frontiers in Education, 2022)
The explores the impact of using both ADDIE Model as an instructional design and UDL in planning for English Literature Online courses during COVID-19 in higher education from the perspective of the students. A quantitative approach was used for collecting the data, where a four-part questionnaire was distributed to 90 students, who were randomly chosen from the students of a group of English Literature professors from different public and private universities in Jordan, who were asked to plan for their online English Literature courses through integrating both the ADDIE model, with its principles of Analysis, Design, Development, Implementation, and Evaluation, and Universal Design for Learning (UDL) with its principles of Engagement, Representation, Action and Expression. As a conclusion, the study shows the positive impact of using both ADDIE Instructional Design Model and Universal Design for Learning (UDL) in English Literature Online courses on the students’ performance from the perspective of the students. Up to the researcher’s knowledge, no prior studies have been conducted to explore the effect of the use of ADDIE model and UDL in online English Literature courses for graduate students in universities or other forms of higher education from the perspective of the students.